2019
DOI: 10.32604/jrm.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blueberry and Jaboticaba Agroindustrial Residue Particle Size on Color Change of Corn Starch Based Films Submitted to Different pH Values Solutions

Abstract: Corn starch, glycerol and agroindustrial residues were used to produce films by casting. By-products from juice processing, blueberry and jaboticaba in powder with different particle sizes were added in the filmogenic matrix to evaluate its potential as a colorimetric indicator. Blueberry and jaboticaba peels are commonly discarded although contain high amount of important compounds as anthocyanins. These compounds have the ability to color change after immersion in different pH values, demonstrating its poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
0
0
2
Order By: Relevance
“…Furthermore, incorporating anthocyanin‐rich natural sources like purple potato and various berries (blackberry, blueberry, black chokeberry, jaboticaba) into these films not only enhances their efficacy for intelligent packaging applications but may also amplify their antioxidant activity, potentially contributing to the prolonged freshness of perishable goods. 44 , 45 , 46 , 47 , 48 , 49 Notably, anthocyanins extracted from red cabbage and black carrots are widely used in the creation of intelligent packaging. Numerous studies have demonstrated their efficacy in detecting spoilage in seafood such as fish and shrimp, pasteurized milk and in sensing environmental changes.…”
Section: Natural Colourimetric Sensors and Their Applicationsmentioning
confidence: 99%
“…Furthermore, incorporating anthocyanin‐rich natural sources like purple potato and various berries (blackberry, blueberry, black chokeberry, jaboticaba) into these films not only enhances their efficacy for intelligent packaging applications but may also amplify their antioxidant activity, potentially contributing to the prolonged freshness of perishable goods. 44 , 45 , 46 , 47 , 48 , 49 Notably, anthocyanins extracted from red cabbage and black carrots are widely used in the creation of intelligent packaging. Numerous studies have demonstrated their efficacy in detecting spoilage in seafood such as fish and shrimp, pasteurized milk and in sensing environmental changes.…”
Section: Natural Colourimetric Sensors and Their Applicationsmentioning
confidence: 99%
“…Atualmente, resíduos agroindustriais podem ser utilizados na produção de ração animal, biocombustível, compostos bioativos, enzimas, entre outros bioprodutos (Sharma et al, 2021;Velarde et al, 2020;Takeyama et al, 2020; sendo, uma promissora alternativa o uso desses resíduos para desenvolvimento de filmes biodegradáveis (Luchese et al, 2021;Luchese et al, 2019) e filmes nanocompósitos (Coelho et al, 2020;Pelissari et al, 2017;Balakrishnan et al, 2017) com potencial aplicação como embalagem ativa (Crizel et al, 2018;Crizel et al, 2016). Nesse sentido, considerando a proeminente geração de resíduos alimentares no Brasil (Santos et al, 2020;Dal' Magro & Talamini, 2019), tais como resíduos de acerola, goiaba, abacaxi, caju, uva, laranja, mamão, maracujá, mandioca (Takeyama et al, 2020;Andrade et al, 2017;Silva et al, 2014;Souza et al, 2011), há potencialidade de valorização destes resíduos vegetais para o desenvolvimento de filmes, dado riqueza de componentes hábeis para formação de uma matriz polimérica (Souza et al, 2021;Acquavia et al, 2021;Otoni et al, 2017).…”
Section: Perda E Desperdício De Alimentos: Importância Do Aproveitamento De Resíduos Vegetaisunclassified
“…Ademais, o uso de plastificantes, como glicerol, pode ser necessário para formação de uma matriz contínua e melhora das propriedades mecânicas, uma vez que interferem na ligação de hidrogênio (Acquavia et al, 2020;Maraveas, 2020) e na interação macromolecular durante o rearranjo da amilopectina ou amilose (Fu et al, 2018). O amido de diferentes fontes vegetais e seus resíduos foram explorados para a elaboração de filmes, tais como amido de mandioca (Luchese et al, 2021;Huang et al, 2020), de arroz (Suriyatem et al, 2018), de quinoa (Pagno et al, 2015), de milho (Luchese et al, 2019), de araruta (Nascimento et al, 2021;Nogueira et al, 2019), de batata (Balakrishnan et al, 2017), de semente de jaca (Costa et al, 2021), semente de manga (Silva et al, 2019), de polpa de banana (Pelissari et al, 2017) e de polpa de maçã (Tirado-Gallegos et al, 2018).…”
Section: Biopolímeros Extraídos De Resíduos Agroindustriais: Matéria-prima Para Elaboração De Filmesunclassified